Dialogism between interspersed genres in the narrative The Hobbit, by J.R.R. Tolkien - Ponte, Charles Albuquerque; Nazário, Ismael Arruda; Martins, Jailma Pereira (Literartes, 2020)
The narrative present in The Hobbit, by J. R. R. Tolkien, is composed ofvaried songs that dialogue with the plot being developed. This connection is important because it promotes a content communication between those and the story. Thus, we aim, in this article, to investigate the relations between the two genres from a dialogical perspective. We will show how the contents of the poems relate to the events of the narrative. We will mainly use Bakhtin’s (1992 and 2015) works on the dialogism betweenthe different discourses, and the intercalated genres, and the work by Brait (2005) concerning dialogism. We selected two poems and analyzed their contents. After the analysis, we understand that the poems are fundamental to the internal dynamics of the story, dialoguing with it in many points, giving support in the presentation in the narratedevents.